Analysis of selected physical and performance attributes of the United States Olympic team handball players: Preliminary study - Bergemann, B. (The Sport Journal, 1999)
During the Spring of 1995, prior to the Olympic Games in Atlanta, the United States Team Handball team and coaches came to the United States Sports Academy in Daphne, AL for testing. Dr. Thomas P. Rosandich, president of the U.S. Team Handball Federation, and the president of the United States Sports Academy hosted the testing at the Alabama campus. Testing of the athletes consisted of laboratory tests of maximum oxygen uptake, computerized strength measures, blood tests, etc., and a battery of field tests that included assessments of physical characteristics, and physical performance components. This paper reports the results of the field test battery. Skills test batteries have been used in physical education and in sport to assess various components of the skills of players. These assessments served the teacher and coach to determine a player's level of ability, or their progress, weaknesses and strengths. These test batteries for sports performance usually dealt with the physical fitness components like strength and endurance, or the motor skills components, like speed, agility, power, or accuracy. Batteries of tests for team handball have not been developed in the United States. The purpose of this investigation was to construct a team handball test battery that would be reflective of the skills, abilities, physical fitness components and anthropometric factors that contribute to high levels of performance, and to establish a database of performances by the National Team Handball players. Additional purposes for developing the test included using the test to screen potential players at the National level, to provide teachers in the schools and colleges with tests that are inexpensive and easy to administer, and to provide self-administered tests that would train the athletes to improve their performance in team handball.